Hukum Pernikahan Janda Dalam Masa ‘Iddah Menurut Pandangan Ulama Palangka Raya - Jauharatun Jauharatun (LP2M IAIN Palangka Raya, 2016)
The begraund of this research is widow marriage law in the ‘iddah period according to Palangka Raya religious adviser on religious law. The fact is the woman completed the trial court divorce then remarry without spending that ‘iddah period consistently. The objective of this research are: How is the law status widow marriage in the ‘iddah period according to religious adviser on religious law? What is law used to answer the problem of widow marriage in the ‘iddah period according to religious adviser on religious law?. This study is sociological law research or empirical which use descriptive qualitative approach. The data is collected by interviewing and documentation and validated with source triangulation technique. The data analyzed in three steps are reduction, display and conclusion drawing/classification. The result of this research conclude that: According Palangka Raya religious adviser on religious law widow marriage in the ‘iddah period is haram because it is imperfect which caused damaged to one of the conditions of marriage. The most important widow marriage legals in the waiting period are Al-Qur’an, Surah At-Thalaq paragraphs 1, 2, 4, 6, dan 7 and Surah Al-Baqarah paragraphs 228-234. There is provision of marriage law in Indonesia number 1 of 1974.